2018
DOI: 10.1016/j.redox.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin-2 controls cardiac mitochondrial dynamics and energetics in mice, and protects against human cardiac pathologies

Abstract: Glutaredoxin 2 (GRX2), a mitochondrial glutathione-dependent oxidoreductase, is central to glutathione homeostasis and mitochondrial redox, which is crucial in highly metabolic tissues like the heart. Previous research showed that absence of Grx2, leads to impaired mitochondrial complex I function, hypertension and cardiac hypertrophy in mice but the impact on mitochondrial structure and function in intact cardiomyocytes and in humans has not been explored. We hypothesized that Grx2 controls cardiac mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…As mentioned, this is the first time the impact of GRX2 deficiency on mitochondrial O 2 •- /H 2 O 2 release from individual sites of production was ever quantified. Previous reports had found that partial or full deletion of the Grx2 results in the over S-glutathionylation of the mitochondrial proteome, increased S-glutathionylation of complex I, and the development of signs of heart disease including left ventricular hypertrophy, mitochondrial fragmentation, fibrosis, and hypertension [11] , [43] . Intriguingly, these effects are not associated with oxidative distress or damage [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, this is the first time the impact of GRX2 deficiency on mitochondrial O 2 •- /H 2 O 2 release from individual sites of production was ever quantified. Previous reports had found that partial or full deletion of the Grx2 results in the over S-glutathionylation of the mitochondrial proteome, increased S-glutathionylation of complex I, and the development of signs of heart disease including left ventricular hypertrophy, mitochondrial fragmentation, fibrosis, and hypertension [11] , [43] . Intriguingly, these effects are not associated with oxidative distress or damage [11] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, GRX2 deficiency leads to the development of cataracts, signs of heart disease, hypertension, and perturbs embryonic development [11] , [15] , [16] . It has also recently been shown to play a role in regulating mitochondrial morphology and low GRX2 transcript levels correlates with development of heart disease in humans [17] . This is associated with impaired mitochondrial ATP production and higher than normal ROS production rates [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Grx2a over-expression decreased susceptibility towards apoptosis induced by doxorubicin (DOX) [ 100 ]. Grx2 is essential for mitochondrial morphology and dynamics in cardiomyocytes in humans and mice [ 101 ]. The loss of mitochondrial Grx2 is connected to increased mitochondrial proton leaks and respiration in muscle cells [ 102 ].…”
Section: Glutathione Glutaredoxins and Iron-metabolismmentioning
confidence: 99%
“…A section of the left ventricular free wall was dissected and immediately placed in ice-cold preservation medium (BIOPS; containing 2.77 mM CaK2EGTA, 7.23 mM K2EGTA, 5.77 mM Na2ATP, 6.56 mM MgCl2•6H2O, 20 mM taurine, 15 mM phosphocreatine, 20 mM imidazole, 0.5 mM dithiothreitol, and mM 4-morpholine-ethanesulfonic acid, pH 7.1) for mechanical separation with fine forceps under a dissecting microscope. Separated fibre bundles were incubated in BIOPS containing 5 mg/mL saponin for 30 min at 4°C and then transferred to respiration medium (MiR05; containing 0.5 mM EGTA, 3 mM MgCl2•6H2O, 20 mM taurine, 10 mM K2HPO4, 20 mM HEPES, 110 mM sucrose 60 K-lactobionate, and 1 g/L BSA, essentially fatty acid free in sterile water, pH 7.1) for three 15 min washes at 4° C (Kanaan et al, 2018).…”
Section: Permeabilized Muscle Fibre Bundle Preparationmentioning
confidence: 99%